2006
DOI: 10.1161/01.str.0000199034.26345.bc
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Hemoglobin A 1c and C-Reactive Protein on the Progression of Subclinical Carotid Atherosclerosis

Abstract: Background and Purpose-Glycohemoglobin (hemoglobin A 1c [HbA 1c ]) and high-sensitivity C-reactive protein (hsCRP) are risk indicators for atherosclerosis. Limited information exists regarding the combined effects of inflammation and hyperglycemia. We investigated the joint effects of both parameters on early carotid atherosclerosis progression and major vascular events in diabetic and nondiabetic subjects. Methods-We analyzed the data of INVADE (Intervention Project on Cerebrovascular Diseases and Dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 36 publications
8
71
0
5
Order By: Relevance
“…Several studies have examined the relation between hsCRP and CCA-IMT in patients with type 2 diabetes mellitus [10,11,17]. However, there are no data on whether hs-CRP is a better predictor for subclinical atherosclerosis relative to other factors directly associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the relation between hsCRP and CCA-IMT in patients with type 2 diabetes mellitus [10,11,17]. However, there are no data on whether hs-CRP is a better predictor for subclinical atherosclerosis relative to other factors directly associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no data on whether hs-CRP is a better predictor for subclinical atherosclerosis relative to other factors directly associated with insulin resistance. Recently, Sander et al reported that hs-CRP is one determinant of CCA-IMT as evaluated by multiple regression analysis [10]. However, indexes of insulin resistance such as HOMA-IR and fasting insulin were not included in their analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is embedded in the CMCS, a nationwide population-based study that aimed to investigate risk factors related to the incidence of CVD 13) . Of the 1,982 subjects originally selected for the CMCS trial using stratified random sampling for each sex and 10-year age group in a community in Beijing in 1992, 1,324 subjects ranging from 45 to 74 years of age took part in an examination of cardiovascular risk factors and carotid B-mode ultrasound in veys 15) . The presence of plaque was defined as an IMT of ≥ 1.3 mm or a focal structure that encroached into the arterial lumen measuring at least 0.5 mm or 50% of the surrounding IMT.…”
Section: Participantsmentioning
confidence: 99%
“…CRP is marked as an independent predictor of future CVD events [14][15][16]. Therefore, this pro-inflammatory phenotype may underlie the association between liver fat and CVD risk.…”
Section: Introductionmentioning
confidence: 99%